A New species of Parasitic copepod, Nemesis santhadevii (Siphonostomatoida: Eudactylinidae) from the gills of the Coral catshark Atelomycterus marmoratus, from Kota Kinabalu, Malaysia - Balu Alagar Venmathi Maran; Panakkool Thamban Aneesh; Moon, Seong Yong (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
The copepod Nemesis santhadevii sp. nov. (Siphonostomatoida: Eudactylinidae), which is parasitizing the gill filaments of the Coral catshark Atelomycterus marmoratus (Anonymous (Bennett), 1830) off Kota Kinabalu waters, Malaysia, is described and illustrated in this article. The new species Nemesis santhadevii prominently differs from its congeners in the following features: (1) the cephalothorax sub-circular is 1.3 times as wide as long and overlapping the second pedigerous somite; (2) the fifth somite is 0.4 times the width of the fourth; (3) the genital double somite is slightly narrower than the fifth; (4) the lowest cephalothoracic shield’s body length (0.20:1) proportion; (5) the caudal rami is ovate, it has two large and three small setae; (6) and the second somite has antenna with a patch of 34–38 spinules. It is the first record of parasitic eudactilinid copepod from Sabah, East Malaysia. A checklist of global valid species of Nemesis Risso, 1826, is provided.